Workforce Management Evaluation at Adinda Parinring Kindergarten Makassar - Sofyan, Sofyan; Siraj, Arifuddin; Mardyawati, Mardyawati (Program Pascasarjana Universitas Negeri Makassar, 2019)
This study describes how the Workforce management evaluation at Adinda Parinring Makassar kindergarten is specifically the implementation of the management of the teaching staff. To obtain answers to these problems, the authors use three methods of data collection; Observations, interviews and documentation. In field research the author uses observation and interview instruments. Qualitative data processing and data analysis techniques that I use are; Data reduction, data discovery and data verification. The samples in this study were all educators in Adinda Parinring Makassar kindergarten. The results of the study show that the evaluation and follow-up of educators in Adinda Parinring Kindergarten are conducted regularly, ie every week and at the end of each semester.Â Â